The Spread of Gig Economy: Trends and Effects - Nilanjan Banik; Milind Padalkar (Foresight and STI Governance)
The development of online communication platforms has given rise to the phenomenon of the gig economy. A new economic model that embraces a variety of forms of short-term employment is rapidly spreading around the world, becoming an everyday reality and transforming the labor market. The article analyzes the factors influencing the dynamics of this process and its main effects. Testing the main hypothesis showed that the development of technological infrastructure, despite its importance, does not fully explain the unevenness of the penetration of the gig economy and the variations in its impact upon different sectors, professions, and skill levels. Gig economy drivers are subject to further study, but already now we can state the need for targeted measures to adapt the economy to the new model, including retraining or creating alternative employment opportunities for “traditional” workers giving up jobs in favor of gig-employed ones.